The Impact of Digital Transformation on Service Quality in Nepal’s Restaurant Industry: Balancing Technology and Human Touch - Shrestha, Jhamka Narayan; Pandit, Shishir; Sharma, Aaditya Shankar; Devkota, Jiwan (NPRC Journal of Multidisciplinary Research, 2025)
Background: The rapid growth of digital payment systems and increasing customer expectations in the hospitality sector have made service quality a critical factor for business success. Understanding customer perceptions of restaurant services is essential for improving satisfaction and loyalty. Objective: This study aims to analyze customer perceptions of service quality in restaurants, focusing on factors such as tangibles, reliability, responsiveness, assurance, and empathy, and their impact on satisfaction and revisit intentions. Method: A quantitative survey was conducted among 130 restaurant customers in Nepal, using a structured questionnaire. Data were analyzed using descriptive statistics to assess responses on service quality dimensions and overall satisfaction. Findings: The results indicate strong customer agreement on the importance of well-maintained facilities (39.5% strongly agree), professional employee behavior (41.9% strongly agree), and prompt service (41.5% strongly agree). Neutral responses in areas like operating hours (26.8% neutral) and food/wine knowledge (18.1% neutral) suggest areas for improvement. Overall, 43.7% of customers agreed they were satisfied, and 42.2% planned to revisit. Conclusion: The study confirms that key service quality dimensions significantly influence customer satisfaction. However, enhancing employee expertise and operational flexibility could further improve loyalty and recommendations. Novelty: This research provides localized insights into Nepalese customers' service quality expectations, contributing to the limited literature on hospitality management in emerging markets.